AB0400 Intravenous Golimumab Inhibits Radiographic Progression and Maintains Clinical Efficacy and Safety in Patients with Active Rheumatoid Arthritis despite Methotrexate Therapy: 2-Year Results of A Phase 3 TRIAL of Intravenous Golimumab. (10th June 2014) - Weinblatt, M.E.; Bingham, C.O.; Mendelsohn, A.M.; Kim, L.; Lo, K.H.; Noonan, L.; Baker, D.; Westhovens, R.
Abstract : Objectives: To evaluate long-term clinical/radiographic efficacy of IV GLM 2mg/kg+MTX in active RA despite MTX through wk112. Methods: 592 pts with active RA (≥6/66 SJC, ≥6/68 TJC, CRP≥1.0mg/dL, RF and/or anti-CCP positive) despite ≥3 months of MTX (15-25mg/wk) participated in this multicenter, randomized, double-blind, placebo (PBO)-controlled study. Pts were randomized to IV GLM 2mg/kg or PBO at wks0&4 and q8wks; all pts continued stable MTX. PBO pts with <10% improvement in SJC+TJC at wk16 could early escape to IV GLM 2mg/kg (wks16&20, q8wks). All PBO pts received IV GLM 2mg/kg starting at wk24. Primary endpoint was wk14 ACR20. Radiographs of hands and feet at wks 0, 24 (wk16, early escape), 52, and 100 were scored by 2 independent readers and adjudicator (as needed) using the vdH-S score. Reading Session 2 included wk0, wk52, and wk100 scores. In general, analyses at wks 24, 52, and 100 were performed using ITT methodology, with imputation for missing data. Results: 82% of pts (486/592) continued through wk112; 106 pts d/c, mostly due to AEs (44pts) and few due to lack of efficacy (12pts). At wk14, significantly (p<0.001) larger proportions of GLM+MTX vs PBO+MTX pts had ACR20/50/70, DAS28-CRP good/moderate responses, and greater improvements in HAQ. Clinical improvements were maintained through wk100 (final efficacy visit), when ACR20/50/70 responses among all GLM+MTX-treated pts were 68.1%, 43.8%, and 23.5%, resp; DAS28-CRP moderate/good response was 81.9%; and median improvement from wk0 in HAQ was 0.5; 67.1% of GLM+MTX pts had improvement in HAQ ≥0.25 from baseline. GLM+MTX-treated pts continued to have significantly less radiographic progression based on vdH-S total and subscores vs PBO+MTX at wk24, and PBO+MTX$→ $GLM + MTX at wk52 and wk100. Pts randomized to PBO+MTX who began GLM at wk16/24 demonstrated marked slowing of radiographic progression from wk24-52 and from wk52-100. Through wk112 (final safety visit), the mean follow-up for all GLM-treated pts was 96wks. AEs and serious AEs occurred in 79% and 18%, resp, of GLM-treated pts (vs 49% and 2% at wk24). 3 cases of TB and 2 serious opportunistic infections (cryptococcal pneumonia, intervertebral discitis) were reported through wk112. 6pts (1.0%) died: 1 PBO+MTX and 5 (0.8%) GLM+MTX (pneumonia/MI, dehydration, abdominal TB, unknown x 2). Through wk112, the proportion of infusions with infusion reactions was 0.4% and the proportion of pts with infusion reactions was 3.9% (vs. 1.1% and 3.5%, respectively, at wk24). Conclusions: IV GLM+MTX significantly inhibited radiographic progression (vdH-S scores) at wks 24, 52 and 100. Among PBO-treated pts who began GLM at wk16/24, marked slowing of radiographic progression, to rates similar to pts randomized to GLM, was observed from wk24-52 and from wk52-100. IV GLM+MTX also significantly improved and maintained RA signs/symptoms in pts with active RA despite ongoing MTX and continued to demonstrate an acceptable safety profile through wk112. Disclosure of Interest: M. Weinblatt: None declared, C. Bingham III: None declared, A. Mendelsohn Employee of: Janssen Research & Development, LLC., L. Kim Employee of: Janssen Research & Development, LLC., K. Lo Employee of: Janssen Research & Development, LLC., L. Noonan Employee of: Janssen Research & Development, LLC., D. Baker Employee of: Janssen Research & Development, LLC., R. Westhovens: None declared DOI: 10.1136/annrheumdis-2014-eular.2049